A Second Wave? What Do People Mean by COVID Waves? – A Working Definition of Epidemic Waves - Zhang SX; Arroyo Marioli F; Gao R; Wang S (Dove Medical Press, 2021)
Stephen X Zhang,1 Francisco Arroyo Marioli,2 Renfei Gao,3 Senhu Wang4 1Faculty of Professions, University of Adelaide, Adelaide, SA, Australia; 2Central Bank of Chile, Santiago, Chile; 3Manchester Business School, University of Manchester, Manchester, UK; 4Department of Sociology and the Centre for Family and Population Research, National University of Singapore, SingaporeCorrespondence: Stephen X Zhang Email Stephen.x.zhang@gmail.comIntroduction: Policymakers and researchers describe the COVID-19 epidemics by waves without a common vocabulary on what constitutes an epidemic wave, either in terms of a working definition or operationalization, causing inconsistencies and confusions. A working definition and operationalization can be helpful to characterize and communicate about epidemics.Methods: We propose a working definition of epidemic waves in the ongoing COVID-19 pandemic and an operationalization based on the public data of the effective reproduction number R.Results: Our operationalization characterizes the numbers and durations of waves (upward and downward) in 179 countries.Discussions: The proposed working definition of epidemic waves provides a common and consistent vocabulary that can enable healthcare organizations and policymakers to make better description and assessment of the COVID crisis to make more informed resource planning, mobilization, and allocation temporally in the continued COVID-19 pandemic.Keywords: COVID wave, epidemic wave, second wave, epidemiology, infection